Experimental Steps for Calibrating a Radon Meter for Use in Environmental Studies - Barbosa, Eder Queiroz [UNESP]; Bonotto, Daniel Marcos [UNESP] (My University, 2020)
Potential health hazards from radon in consuming water have been considered worldwide, with many countries adopting the guideline activity concentration of 100 Bq/L for drinking water quality as proposed in the past by WHO. Radon is quickly absorbed by inhalation, through mucous membranes, rather than by bathing. In general, such recommendation was applied to routine operational conditions of water supply systems despite special attention was given if ground waters are utilized for public water supplies as their 222Rn levels are commonly 10-100 times higher than the values in surface waters (often less than 3.7 Bq/L). Typically, about 70% to 90% of the radon gas dissolved in water escapes into the atmosphere, implying on the requirement of water possessing 10, 000 Bq/L of dissolved 222Rn for each 1Bq/L in the air. Thus, an indoor environment with water containing 1, 000 Bq/L of dissolved 222Rn will contribute to the radon release into the air of about 100 Bq/m3. All these aspects indicate that environmental studies focusing the presence of radon in the atmosphere and waters require properly calibrated equipments based on standardized procedures as the data generated will be compared with guideline reference values for health risks at different national and international levels. A wide range of systems have been developed for the radon measurements elsewhere and this chapter describes a set of laboratorial experiments held in order to reach this purpose for the Pylon AB6A that is a equipment employing a scintillation detector consisting of a Lucas cell coupled to a photomultiplier tube.
Keywords: Continuous analysis method; Lucas cell; Pylon radon meter; Quasi analysis method; Scintillation technique